Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.